2013
DOI: 10.1074/mcp.m112.021303
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Populations of Exosomes Are Released from LIM1863 Colon Carcinoma Cell-derived Organoids

Abstract: Exosomes are naturally occurring biological nanomembranous vesicles (ϳ40 to 100 nm) of endocytic origin that are released from diverse cell types into the extracellular space. They have pleiotropic functions such as antigen presentation and intercellular transfer of protein cargo, mRNA, microRNA, lipids, and oncogenic potential. Here we describe the isolation, via sequential immunocapture using anti-A33-and anti-EpCAM-coupled magnetic beads, of two distinct populations of exosomes released from organoids deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
361
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 374 publications
(392 citation statements)
references
References 65 publications
(70 reference statements)
11
361
0
3
Order By: Relevance
“…Since a previous study has reported expression of ANXA1 by neutrophilderived EVs (8), we predict that in the local microenvironment of the wound, ANXA1-containing EVs might be derived not only from infiltrating leukocytes but also from the repairing epithelium. In fact, we demonstrated the presence of ANXA1-containing EVs that colabeled with an epithelial-derived protein, A33, in ex vivo cultures of wounds (55). In conclusion, detection of ANXA1-containing EVs in the serum could serve as a biomarker for active mucosal inflammation (56).…”
Section: Anxa1 Released In Intestinal Epithelialmentioning
confidence: 84%
“…Since a previous study has reported expression of ANXA1 by neutrophilderived EVs (8), we predict that in the local microenvironment of the wound, ANXA1-containing EVs might be derived not only from infiltrating leukocytes but also from the repairing epithelium. In fact, we demonstrated the presence of ANXA1-containing EVs that colabeled with an epithelial-derived protein, A33, in ex vivo cultures of wounds (55). In conclusion, detection of ANXA1-containing EVs in the serum could serve as a biomarker for active mucosal inflammation (56).…”
Section: Anxa1 Released In Intestinal Epithelialmentioning
confidence: 84%
“…Western Blot Analysis-Exosome samples (ϳ10 g protein) were prepared for Western blot analysis as previously described (44). Membranes were probed with primary mouse anti-TSG101 (BD Transduction Laboratories; 1:500), mouse anti-Alix (Cell Signaling Technology, Daanvers, MA; 1:1000), mouse anti-H-Ras (Santa Cruz Biotechnology, Santa Cruz, CA; 1:500), mouse anti-E-cadherin (BD Transduction Laboratories; 1:1000), rabbit anti-EpCAM (Abcam, Cambridge, MA; 1:1000), rabbit anti-MMP-1 (Santa Cruz Biotechnology; 1:200), rabbit anti-YB-1(YBX1) (Abcam; 1:500) or mouse antivimentin (Merck-Millipore; 1:500), for 1 h in TTBS (50 mM Tris, pH 7, 150 mM NaCl, 0.05% (v/v Tween 20) followed by incubation with the secondary antibody, IRDye 800 goat anti-mouse IgG or IRDye 700 goat anti-rabbit IgG (1:15000, LI-COR Biosciences, Lincoln, NE, USA), for 1 h in darkness.…”
Section: Methodsmentioning
confidence: 99%
“…Depending upon the source, the exosome populations have been shown to range in size as well as protein content (38,39). Heterogeneous populations of exosomes have also been identified from cancerous cell types, including colon cancer (40).…”
mentioning
confidence: 99%